Analysis of crystallograms of oral fluid in the dynamics of treatment of patients with pathology of the oral mucosa - Yu. A. Makedonova; E. S. Aleksandrina; S. V. Dyachenko; O. Yu. Afanayeva; O. N. Kurkina (Эндодонтия Today, 2022)
One of the express diagnostic methods is a crystallographic study of the oral fluid of this category of patients. Based on the quantitative and qualitative criteria of saliva obtained by the method of wedge dehydration, it is possible to non-invasively assess the effectiveness of the therapy and timely correct the prescribed treatment.Aim. To conduct a comparative analysis of the crystallograms of the oral fluid in the dynamics of the treatment of patients with pathology of the oral mucosa.Materials and methods. 90 patients were examined with a diagnosis of K12.00 aphthous stomatitis (small), chronic recurrent aphthous stomatitis (mild form). All patients were divided into 3 groups according to the methods of therapy 1:1:1 according to the principle of randomization. To assess the state of the oral fluid of patients with aphthous stomatitis against the background of various methods of treatment, the method of wedge-shaped dehydration was used, where the transition of a drying biological fluid into a solid state leads to a certain static order that can be observed and studied. Saliva was used as the material for the study.Results. A qualitative analysis of the crystallograms revealed various types of structures with inclusions of bent prismatic crystals. Prismatic, fragmentary, curved, X-shaped, skeletal types of crystals were found throughout the entire field of view. At the same time, there was no clear structured picture as a result of a violation of the normal crystallization process.Conclusion. There is a clear need for further research into the molecular etiopathogenesis of these conditions, which should allow the identification of more specific molecular targets for the development of diagnostic tests and therapeutic intervention. Based on the data obtained, the wedge dehydration method used for crystallographic examination of the oral fluid objectively reflects the state of the oral mucosa and can be used as an additional non-invasive method for diagnosing inflammatory and destructive diseases of the oral mucosa, as well as for correcting the treatment plan and monitoring the results of therapy.